KETERAMPILAN TEKNIS YANG DIBUTUHKAN OLEH USAHA JASA KONSTRUKSI DI KOTA PADANG - 314-319 , Liza Sartika (Universitas Negeri Padang, 2014)
ABSTRACT This research is motivated by the increasing number of civil engineering graduates from various universities annually which will make the competition tight semakn college graduates . It is also triggered by the limited acceptance of the workers at the construction company as a contractor in the cityofPadang. This study was descriptive quantitative aimed to obtain information about the technical skills required contractors on construction services business in the city of Padang . The study population was a member of Padang GAPENSI year 2012/2013 , with a sample size of 16 companies Grade 6 and 7 . Techniques for collecting data was a questionnaire with Likert scale models that have been tested for validity and reliability. Data processing was done by usingapercentage. The results of this study showed that as many as 4 out of 24 technical skills required by the contractor, the technical skills are: autocad drawing skills with a frequency of 14 (87.5%), counting skills with frequency Budget Plan 13 (81.3%) and skills structural analysis of the frequency of 9 (56.3%). While other technical skills that are at a frequency of ≤ 8 (≤ 50%) expressed less needed by the contractor, the technical skills are: basic practice of building, 2nd floor Bestek, image projection, image construction elements, principles of statics, simple measuring devices, utility buildings simple, theodolite, carpentry, masonry and concrete, plumbing and sanitation, GPS, soil classification, testing concreate aggregate mix design, soil properties, bangunanan quality materials, electro-distance tool (EDM), optical leveling instruments, fluid and tools optics. Key words : technical skills , contractors , construction services business